Advances in drug therapy and delivery for cataract treatment. Issue 1 (14th January 2023) - Lee, Bryanna J.; Afshari, Natalie A.
Abstract : Purpose of review: Cataract is one of the leading causes of blindness worldwide and surgery is the only available treatment. Pharmacological therapy has emerged as a potential approach to combat the global shortage of surgery due to a lack of access and resources. This review summarizes recent findings in pharmacological treatment and delivery, focusing on drugs that target oxidative stress and the aggregation of crystallins. Recent findings: Antioxidants and oxysterols have been shown to improve or reverse lens opacity in cataract models. N-acetylcysteine amide and N-acetylcarnosine are two compounds that have increased bioavailability over their precursors, alleviating the challenges that have come with topical administration. Studies have shown promising results, with topical N-acetylcarnosine clinically decreasing lens opacity. Furthermore, lanosterol, and more recently 5-cholesten-3b, 25-diol (VP1-001), have been reported to combat the aggregation of crystallins in vivo and ex vivo . Delivery has improved with the use of nanotechnology, but further research is needed to solidify these compounds' therapeutic effects on cataracts and improve delivery methods to the lens. Summary: Although further research in drug dosage, delivery, and mechanisms will need to be conducted, pharmacologic therapies have provided new strategies and treatments for the reversal of cataracts.